PENGARUH WORD OF MOUTH COMMUNICATION TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN PADA BOARDGAME LOUNGE SMART CAFE PEKANBARU - Yuly Rahmi Pratiwi; Evawani Elysa Lubis (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
of mouth communication is a form of promotion in the form of recommendation by word of mouth about the goodness of a product. Word of mouth communication is very effective in supporting the purchasing decision. The customer in deciding the purchase of products is very influential with the word of mouth communication. This research starts on the stimulus-response theory. In this research Word of mouth communication is the stimulus given by the talkers (speaker/influence) to the recipient regarding the Boardgame lounge smart cafe so that recipients provide a response in the form of purchasing decisions in the Boardgame smart lounge cafe. The purpose of this research is to know the influence of word of mouth communication towards customer purchasing decisions in the Boardgame smart lounge cafe. The methods used in this research is quantitative method of explanation. Data collection techiques in this study using questionnaire. The number of samples for this studi were 96 respondents. Sampling using Accidental Sampling. To find out how much influence both of these variables, the researchers used a simple linear regression analysis. Questionnaire for data processing, carried out using the statistical program Product And Service Solution (SPSS) version of Windows 23. The results of the research on the influence of word of mouth communication with indicators (Talkers, Topics, Tools, Taking Part, Tracking) against purchase decisions with indicators (introduction to the issue, information retrieval, assessment of alternatives, purchasing decisions, the behavior of post purchase) customer on Boardgame lounge smart cafe regression coefficient values obtained in this research is Y = 9.895 + 0.548 X with significance level 0.000 that smaller than α = 0.05. This means that there is the influence of word of mouth communication towards customer purchasing decisions in the Boardgame lounga smart cafe of 50.7% and in the category of influential medium. The percentage indicate that word of mouth communication towards customer purchasing decision in Boardgame lounge smart cafe with H0 is rejected and Ha accepted.